2007
DOI: 10.1590/s0101-20612007000100036
|View full text |Cite
|
Sign up to set email alerts
|

Processamento do queijo coalho regional empregando leite pasteurizado e cultura lática endógena

Abstract: ResumoO objetivo deste trabalho foi estabelecer uma proposta para o processamento do queijo Coalho regional seguindo-se os procedimentos adequados para a obtenção de um produto final de qualidade. Empregou-se leite de vaca padronizado e pasteurizado e culturas láticas endógenas. Foram isoladas, identificadas e caracterizadas culturas láticas endógenas de leite de vaca cru e de queijos Coalho artesanais. Algumas culturas foram avaliadas para a fabricação do queijo Coalho, seguindo-se o fluxograma de fabricação … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
29

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 8 publications
0
7
0
29
Order By: Relevance
“…In order to assess the effect of the essential oil toward the autochthonous microflora of the food matrix, samples of coalho cheeses were prepared using uncooked milk according to the procedure described by Cavalcante et al (2007) with minor changes (Figure 1). The cheeses were divided into five groups: i) cheese added with 20 µg.g -1 of the oil; ii) cheese added with 10 µg.g -1 of the oil; iii) cheese added with 5 µg.g -1 of the oil; iv) cheese added with 2.5 µg.g -1 of the oil; and v) cheese without oil (control).…”
Section: Effect Of Oil In Food Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess the effect of the essential oil toward the autochthonous microflora of the food matrix, samples of coalho cheeses were prepared using uncooked milk according to the procedure described by Cavalcante et al (2007) with minor changes (Figure 1). The cheeses were divided into five groups: i) cheese added with 20 µg.g -1 of the oil; ii) cheese added with 10 µg.g -1 of the oil; iii) cheese added with 5 µg.g -1 of the oil; iv) cheese added with 2.5 µg.g -1 of the oil; and v) cheese without oil (control).…”
Section: Effect Of Oil In Food Matrixmentioning
confidence: 99%
“…In addition of establishing and introducing practices in order to minimize the sources of microbial contamination of coalho cheese during its processing, some authors reported the necessity of evaluating the efficacy of classical and alternative chemical or physical procedures for controlling the microbial growth during its storage (CAVALCANTE et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, o armazenamento, o transporte e a comercialização influenciam nos riscos (CAVALCANTE et al, 2007;FREITAS et al, 2009 A refrigeração constitui em um método simples e prático para inibir a proliferação bacteriana, desta forma as amostras de queijo coalho que estavam conservadas por refrigeração, apresentaram um número menor de coliformes em relação às que estavam a temperatura ambiente.…”
Section: Discussionunclassified
“…A produção do queijo é geralmente realizada de forma artesanal em pequenas e médias indústrias onde as técnicas de boas práticas de produção geralmente são negligenciadas, o que gera um produto de qualidade insatisfatória (CAVALCANTE et al, 2007;ZAFFARI;MELLO;COSTA, 2007;FREITAS FILHO et al, 2009).…”
Section: Introductionunclassified
“…O queijo Coalho é fabricado há mais de 1 século fazendose uso da matéria-prima leite de vaca cru ou pasteurizado, em vários Estados da Região Nordeste do Brasil e é tradicionalmente consumido fresco ou maturado (Cavalcante et al, 2007). Para a produção de 1 kg de queijo são necessário 10 L de leite resultando, com isto, em 9 L de soro, ou seja, cerca de 85 a 95% do volume de leite utilizado na fabricação de queijos resultam em soro, o qual contém aproximadamente metade dos sólidos do leite, sendo eles: proteínas solúveis, nitrogênio não proteico, sais minerais, vitaminas e, principalmente, a lactose (Santos & Ferreira, 2001;Richards, 2002).…”
Section: Introductionunclassified